2012 IEEE International Ultrasonics Symposium 2012
DOI: 10.1109/ultsym.2012.0611
|View full text |Cite
|
Sign up to set email alerts
|

3D Ultrasound palm vein pattern for biometric recognition

Abstract: In this work, an ultrasound technique for achieving 3D palm vein patterns for biometric recognition purposes is proposed and experimentally tested. Commercial ultrasound\ud imaging machine and linear arrays have been employed. Both imaging and power Doppler analysis have been performed to detect veins. The probe is moved in the directional orthogonal to the array by an automated scanning system and at each step a 2D frame is captured and stored to form a 3D matrix.\ud The data from the 3D matrix are elaborated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Additionally, more recent feature extraction techniques based on deep learning [50] or collaborative representation [51] are under investigation. Finally, the possibility of extracting other biometrics like vein pattern [22,23] and inner hand geometry [19] from the same acquired volume, implementing in this way a multimodal system, will be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, more recent feature extraction techniques based on deep learning [50] or collaborative representation [51] are under investigation. Finally, the possibility of extracting other biometrics like vein pattern [22,23] and inner hand geometry [19] from the same acquired volume, implementing in this way a multimodal system, will be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Several sensor technologies applications, including single piezoelectric elements, piezocomposite arrays, and more recently capacitive Micromachined Ultrasonic Transducers (cMUTs) and piezoelectric Micromachined Ultrasonic Transducers (pMUTs), as well as various techniques like pulse-echo, impediography, Doppler analysis, photoacoustics, and acoustic holography [18] have been tested to generate ultrasonic images for biometric recognition. Not only fingerprint, but also hand or finger geometry [19,20], vein pattern [21][22][23], and palmprint have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Results have shown that two kinds of 3D information can be extracted: the 3D profile of the palm, which can be achieved with optical methods based on structured-light imaging as well [87], and palm lines’ depth, which instead can be achieved only with the ultrasound. The same set up was also used to extract, through power Doppler analysis, 3D palm vein patterns [88], which provide improved distinctiveness with respect to 2D vein patterns achievable with classical techniques (see Figure 5).…”
Section: Biometric Systems Based On Pulse-echo Imagingmentioning
confidence: 99%
“…Special help is needed in visualizing the vein pattern effectively, as shared in several literatures regarding the potential light spectrum that can be used for the purpose [2] [8] [11]. Other alternatives in visualizing the vein pattern are motivated by the practice done in the medical field such as the use of X-ray and also ultrasound [11] [12]. Of all the options, the infrared (IR) light seems a promising prospect with regard to the biometric purpose.…”
Section: A Vein Visualization Spectrummentioning
confidence: 99%